Generation Z in the Workforce: How Mental Health Shape Job Satisfaction Through Work Engagement in Indonesia’s Urban - Yuliawan, Eko; Sjaipul, Evilina; Winardi, Muhammad Aziz (Universitas Nahdlatul Ulama Surabaya, 2025)
This study aims to analyze the influence of mental health on job satisfaction mediated by work involvement in Generation Z workers in the Greater Jakarta area. The research approach used was quantitative, with the distribution of questionnaires online through Google Forms to respondents who were included in the age of Gen Z and had at least one year of work experience. The sampling technique used purposive sampling with a total of 110 respondents. Data analysis was carried out using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results showed that mental health had a positive and significant effect on job satisfaction but did not have a significant effect on work engagement. Meanwhile, work involvement has a positive and significant effect on job satisfaction but does not act as a mediating variable between mental health and job satisfaction. These findings indicate that mental health has a direct influence on job satisfaction without intermediary work involvement. Theoretically, this study strengthens the theory of Job Demands-Resources (JD-R) by affirming the role of mental health as a personal resource that contributes to work well-being. In practical terms, the results of this study provide implications for organizations to improve the psychological well-being of employees through mental health support programs and create a conducive work environment for Gen Z workers to achieve optimal job satisfaction.